TRABALHO E TECNOLOGIAS SOCIAIS: AS ASSOCIAÇÕES DE CATADORES NA GERAÇÃO DE TRABALHO E RENDA - Silva, Jorge A. d.; Zimmermann, Ieda; Baldissera, Luci M.; Baldissera, Luciana; Schuch, Marta C. (Salão do Conhecimento, 2013)
Resumo